Scheme Financing Infrastructure Projects Through the India Infrastructure Finance Company - Planning Commission (Planning Commission, 2006)
This initiative addresses the need for providing long-term debt for financing infrastructure projects that typically involve long gestation periods. Debt finance for such projects should be of a sufficient tenure that enables cost recovery across the project life. Indian capital markets, however, arc deficient in long-term debt instruments. Setting up of the India Infrastructure Finance Company (IIFC) is aimed at bridging the gap. Underdeveloped pension and long-term debt markets have restricted the tenure of project finance in India. Most of the available debt is of seven to twelve years’ maturity whereas infrastructure projects require a longer pay back period.
Planning Commission Government of India
Planning Commission Government of India